Pengaruh ESG Risk Ratings dan Firm Value Terhadap Kinerja Keuangan Perusahaan - Rahmawati, Apriana (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to analyze the effect of ESG Risk Ratings and Firm Value on the company's Financial Performance. The object of research is a company listed on the Indonesia Stock Exchange and included in the IDXEGL index. The sample in this study is telecommunications industry companies in 2020 - 2022. Data analysis was performed using simple linear regression using SPSS. The results showed that ESG Risk Ratings negatively affect Financial Performance. Furthermore, the firm value variable has a positive effect on Financial Performance.